Field experimental evidence on hiring discrimination in the German apprenticeship market - Köhler, Ekkehard A. [Verfasser]; Wiemann, Dilara [Verfasser] (My University, 2025)
„Are apprenticeship applicants discriminated against, conditional on the quality of their school performance or conditional on their perceived ethnic background? If so, does prior work experience, business knowledge certificates or even volunteering increase the chances to receive an answer? To explore these questions, we fielded a randomized controlled correspondence trial (RCT) to measure how different foreign names (Turkish, Russian, Arab, Hebrew versus German) and individual performance indicators (school grades, the level of economic education and internship experiences) affect employers’ responsiveness to apprenticeship application inquiries. Our findings, complemented by an employer survey, reveal three key insights: First, significant discrimination persists despite excellent academic credentials from applicants with foreign names. Second, evidence for statistical discrimination emerges as employers interpret identical productivity signals differently based on perceived backgrounds. Third, we find that discrimination varies significantly regionally as well as within sectors. The largest effects occur in rural and less densely populated areas and within the industry and skilled trades sector.” (authors’ abstract; BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 5.3 Personalentwicklung; P 1.5 Migranten; 370; 300; Ausbildungsstellenmarkt; Ausbildungsstellenbewerber; Personalauswahl; Einflussfaktor; Ausländer; Migrant; Qualifikationsniveau; Leistungsfähigkeit; Diskriminierung; Feldforschung